Snowboarding - Preszler, Eric (Mankato, Minnesota : Capstone Press, 2005)
Discusses the sport of snowboarding, including gear needed, tricks, and famous snowboarders.
Includes bibliographical references and index.
Keywords: Snowboarding -- Juvenile literature